The Relationship Between Vitamin D and Activity of Daily Living in the Elderly - Li H; Han D; Wang H; Shu D; Xu L; Hou L; Xu Y; Lai X (International Journal of General Medicine, 2022)
Han Li,1 Dongmei Han,1 Haiyan Wang,2 Dan Shu,1 Lei Xu,1 Liufang Hou,1 Ying Xu,2 Xueli Lai2 1The Rehabilitation Department of Nephrology, The First Rehabilitation Hospital of Shanghai, Shanghai, People’s Republic of China; 2Department of Nephrology, Shanghai Changhai Hospital, Shanghai, People’s Republic of ChinaCorrespondence: Ying Xu; Xueli Lai, Department of Nephrology, Shanghai Changhai Hospital, Shanghai, 200433, People’s Republic of China, Email ying.looy@hotmail.com; laixueli_changhai@163.comObjective: To analyze the association between vitamin D and the performance of activity of daily living in the elderly.Methods: A total of 94 patients over the age of 65 were eligible to participate if they had undergone a bone mineral density test and if they were in a stable health condition. Subjects were further divided into two groups according to activity of daily living (ADL): the score over 40 of the patients as the high ADL group and the below as the low ADL group.Results: According to univariate analysis, the mean of total hip T score, serum creatinine/cystatin C ratio (CCR), and vitamin D were significantly different between the two groups (P=0.024, 0.008, 0.010). Multivariate ORs showed that the CCR (OR: 0.948; 95%CI: 0.910– 0.989; P=0.013) and vitamin D (OR: 865; 95%CI: 0.752– 0.994; P=0.047) were inversely associated with having low ADL. Furthermore, on multiple linear regression analysis, the Barthel ADL index was related to geriatric nutritional risk index (GNRI), CCR and vitamin D but independent of patients’ age with the slope of 0.732, 0.539, and 0.689 separately, reflected the stronger relative within the variables.Conclusion: We demonstrated that there is a negative correlation of CCR and vitamin D with having low ADL in elderly population. Monitoring the trend of serum vitamin D and CCR, may have a role in the early detection of low ADL with loss of muscle mass and strength in the population of the elderly.Keywords: vitamin D, CCR, elderly, ADL, muscle mass